2005
DOI: 10.1203/01.pdr.0000185132.38209.73
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Exposure in Preterm Babies Predicts Saliva Cortisol Response to Immunization at 4 Months

Abstract: Preterm babies are exposed to multiple stressors and this may have long-term effects. In particular, high levels of endogenous cortisol might have a programming effect on the hypothalamicpituitary-adrenal axis as may administered glucocorticoids. In this study, we aimed to test the hypothesis that the level of endogenous and exogenous glucocorticoid exposure during the neonatal period predicts the saliva cortisol response to immunization at 4 mo of age. We followed 45 babies born below 32 wk gestation. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 30 publications
4
54
0
1
Order By: Relevance
“…Ashwood et al found that 38% of preterm infants receiving a single course of GCs had a suppressed cortisol response, while 68% of infants receiving a repeat course showed suppression. The only other study of which we are aware found that antenatal GCs predicted a suppressed cortisol response at 4 months postnatal in response to immunization (Glover, Miles, Matta, Modi, & Stevenson, 2005). These consistent findings of suppression among GC-exposed preterm infants could stem from enhanced negative feedback on the HPA axis as a result of fetal GC exposure and/or increased tissue sensitivity to GCs (Harris & Seckl, 2011).…”
supporting
confidence: 65%
“…Ashwood et al found that 38% of preterm infants receiving a single course of GCs had a suppressed cortisol response, while 68% of infants receiving a repeat course showed suppression. The only other study of which we are aware found that antenatal GCs predicted a suppressed cortisol response at 4 months postnatal in response to immunization (Glover, Miles, Matta, Modi, & Stevenson, 2005). These consistent findings of suppression among GC-exposed preterm infants could stem from enhanced negative feedback on the HPA axis as a result of fetal GC exposure and/or increased tissue sensitivity to GCs (Harris & Seckl, 2011).…”
supporting
confidence: 65%
“…Both fetal and maternal serum levels of cortisol increase during gestation and can vary from 20 to 50 nM in the fetal and 200 to 800 nM in the maternal circulations (8,11). Under stress, this can increase two-to threefold (28), and increased cortisol has been associated with problems in fetal growth (7), leading to irreversible reprogramming of the hypothalamic-pituitary-adrenal axis.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, SNAT1 is expressed predominantly in the brain and the placenta (35). SNAT2 shows ubiquitous tissue expression (11) and is associated with the adaptive regulation seen in system A transport under nutritional challenge (9). SNAT4 is predominantly expressed in liver and skeletal muscle (35), with some expression in the human placenta (5).…”
mentioning
confidence: 99%
“…If exposure to androgen occurred 15 days later, near weaning, there was no persistent effect on reproduction. More recent animal studies have focused on poor nutrition in fetal life (for example, isocaloric low-protein diets [31], global nutrient restriction [32,33], and reduced uterine blood flow [34]), maternal stress (in rhesus monkeys [35,36] and pigs [37]) and exposure to various pharmacological agents (such as antenatal glucocorticoids [38][39][40][41]). Other studies compare outcomes resulting from insults during fetal life with insults occurring during early postnatal life [42,43].…”
Section: Principles 1 Andmentioning
confidence: 99%